Insights into the mechanisms governing P01 scorpion toxin effect against U87 glioblastoma cells oncogenesis - Mlayah-Bellalouna, Saoussen; Aissaoui-Zid, Dorra; Chantome, Aurelie; Jebali, Jed; Souid, Soumaya; Ayedi, Emna; Mejdoub, Hafedh; Belghazi, Maya; Marrakchi, Naziha; Essafi-Benkhadir, Khadija; Vandier, Christophe; Srairi-Abid, Najet (Frontiers in Pharmacology, 2023)
The emerging concept of small conductance Ca2+-activated potassium channels (SKCa) as pharmacological target for cancer treatment has significantly increased in recent years. In this study, we isolated the P01 toxin from Androctonus australis (Aa) scorpion venom and investigated its effect on the proliferation and the development of glioblastoma U87, breast MDA-MB231 and colon adenocarcinoma LS174 cancer cell lines. Our results showed that P01 was active only on U87 glioblastoma cells. It inhibited their proliferation, adhesion and migration with IC50 values in the micromolar range. We have also shown that P01 blocked the currents recorded in HEK293 cells expressing SK2 channels with an IC50 value of 3 pM, while it had no effect on those expressing SK3 channels. The investigation of the SKCa channels expression pattern showed that SK2 transcripts were expressed differently in the three cancer cell lines. Particularly, we highlighted the presence of SK2 isoforms in U87 cells, which could explain and rely on the specific activity of P01 on this cell line. These experimental data highlighted the usefulness of scorpion peptides to decipher the role of SKCa channels in the tumorigenesis process, and develop potential therapeutic molecules targeting glioblastoma with high selectivity.